Hubungan Transformasi Digital SDM dengan Resiliensi Organisasi Melalui Moderasi Kepemimpinan Digital dan Budaya Inovasi - Pudjiarti, Emiliana Sri; Setiyaningtiyas, Nerita (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
This study examined the relationship between digital transformation factors (innovation culture, digital leadership, and digital transformation of human resources) and organizational resilience in Indonesian higher education institutions. The research method employed Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach using SmartPLS 4, involving validation of the measurement and structural models through bootstrapping procedures. The findings indicated that all seven hypotheses for direct effects were accepted with statistical significance (p < 0.05), with innovation culture having the strongest influence on organizational adaptive capability (β = 0.356). Mediation analysis confirmed the significant role of organizational adaptive capability as a partial mediator in the transmission of digital transformation's effects on organizational resilience, with indirect effects ranging from 0.079 to 0.108. This study's theoretical contribution enriches the digital transformation literature by validating the dual pathway mechanism and introducing organizational adaptation theory in the context of higher education. Practically, the findings provide a strategic roadmap for higher education institutions to implement a holistic digital transformation strategy by strengthening innovation culture, digital leadership, and human resource digitalization as a foundation for building sustainable organizational resilience.